Menumbuh-kembangkan Potensi Melalui Ekstrakurikuler Seni Kaligrafi Islam Bagi Siswa SD Muhammadiyah Program Khusus Paesan Kecamatan Kedungwuni Kabupaten Pekalongan - Fuad, Asfal; Rosanti, Cholisa; Setianto, Gigih; Sulaiman, Muh Andi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to develop students' potential through extracurricular activities in the art of Islamic calligraphy at Muhammadiyah Elementary School, Paesan Kedungwuni Special Program, Pekalongan Regency. The art of Islamic calligraphy was chosen as a potential development medium because it has high aesthetic value and is able to hone students' fine motor skills, creativity and spiritual understanding. The research method used is descriptive qualitative with a case study approach. Data was collected through observation, interviews and documentation. The research results show that Islamic calligraphy art extracurricular activities significantly contribute to improving students' artistic abilities, strengthening Islamic identity, and building student discipline, perseverance and achievement. Apart from that, this activity also encourages the creation of a conducive learning environment and motivates students to develop their talents and interests in the arts. There are several supporting factors that are key to the success of this activity, namely trainers who provide assistance and provide motivation; and PAI teachers as initiators of ideas, companions, and providing equipment and activity supplies. The inhibiting factors in carrying out this activity are understanding, mental courage of students, and delays in equipment and supplies making the activity less than optimal. This research suggests that schools continue to support and develop extracurricular Islamic calligraphy art programs as an integral part of a holistic educational process.